2022
DOI: 10.1016/j.fmc.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Papel protector de las actuales vacunas para las variantes del virus SARS-CoV-2 y la COVID persistente

Abstract: Puntos para una lectura rápida La COVID-19 persistente es un complejo plurisintomático de difícil manejo clínico. La vacunación por sí sola no es suficiente para controlar la pandemia. La aparición de variantes del SARS-CoV-2 puede condicionar la respuesta vacunal. La variante de mayor interés epidemiológico y la predominante actualmente es la delta. Las vacunas con tecnología ARNm son efectivas contra las variantes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…In addition, vaccines are an important preventive strategy for long COVID (40,42), as they can very effectively prevent severe infections and hospital admissions, which are risk factors for long COVID (43). The likelihood of experiencing symptoms beyond 28 days post-infection is reduced by 50% with the full vaccination schedule.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vaccines are an important preventive strategy for long COVID (40,42), as they can very effectively prevent severe infections and hospital admissions, which are risk factors for long COVID (43). The likelihood of experiencing symptoms beyond 28 days post-infection is reduced by 50% with the full vaccination schedule.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that vaccination has proven to be an important preventive strategy for long COVID, as it is highly effective and efficient in preventing severe infection and hospitalizations due to COVID-19 [ 20 , 21 ]. Additionally, there are medications available for severe forms of COVID-19 that help reduce the risk of hospitalization or death among high-risk individuals [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are medications available for severe forms of COVID-19 that help reduce the risk of hospitalization or death among high-risk individuals [ 22 ]. However, the Ministry of Health in Spain concluded that the potential benefits of vaccination or these medications on the symptoms associated with long COVID are still unclear, although they do not appear to worsen the course of the disease [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a la vacunación, resultó ser un factor protector para síntomas como el dolor articular, dolor abdominal, dolor de espalda, tos, escalofríos, congestión nasal, pérdida de peso, molestias oculares, eritema facial, picor, temblores, mareos, convulsiones, sequedad ocular, dificultad para dormir y palpitaciones. Algunos estudios apuntan en la misma dirección que el nuestro, por lo que la vacunación es útil para mejorar síntomas en personas que ya padecen la enfermedad [209][210][211][212] y pueden evitar muy eficazmente infecciones graves e ingresos hospitalarios [213,214]. Además, no existen pruebas que asocien el COVID persistente con una mayor incidencia de efectos secundarios tras la vacunación [215], ni diferencias en el tipo de vacuna utilizada [209,210,216].…”
Section: Ingreso Hospitalario Y Vacunación Como Factores Predictores ...unclassified